STRATEGI PENENTUAN LOCUS DELICTI TINDAK PIDANA PENEBANGAN POHON TANPA IZIN DI KAWASAN CAGAR ALAM MANINJAU PADA TINGKAT PENYIDIKAN - Pifzen Finot (UNES Journal of Swara Justisia, 2021)
Efforts to Determine Locus Delicti The crime of cutting down trees without permission in the Maninjau Nature Reserve at the Investigation Stage by the Agam Police Unit is to fulfill the material elements of the criminal law regulations that are violated, namely the prohibited act is logging in the prohibited area as contained in Article 82 paragraph (1) letters b and c. In West Sumatra there is a customary community unit that has power over land known as ulayat land. The location where the felled timber is known as the determination of Locus Delicti in forestry crimes. Constraints in Determining Locus Delicti Timber Theft in the Maninjau Nature Reserve at the Investigation Stage by the Criminal Investigation Unit of the Religious Police is a legal factor in which the Criminal Procedure Code (KUHAP) does not regulate with certainty and clearly the method or theory used to determine locus delicti. a criminal act. Another internal factor is the human factor (law enforcement officers), in this case the Police investigator who does not have special expertise in determining the location of the crime of illegal logging, so it requires expert information. Community members are reluctant to be witnesses.